Supplementary Table S2 from Single-Cell Spatial Analysis Identifies Regulators of Brain Tumor–Initiating Cells - Reza Mirzaei (15306062) (2025)
Significant genes in 10 clusters identified through spatial transcriptomics of brain tissues from a GBM mouse model.